Toward a Qur’anic Pedagogy of Tafakkur: Reflective Thinking and Critical Thinking in Qur’an-Hadith Learning - Rizki Amalia Putri; Irwan Ahmad Akbar; Hilyah Ashoumi (ALSYS, 2026)
Qur’an-Hadith learning frequently remains teacher-centered and predominantly informative because Qur’anic concepts have not been sufficiently developed as methodological foundations for instruction, thereby limiting students’ reflective and critical engagement with religious texts. This study aims to construct tafakkur as a Qur’anic pedagogy and explain its relevance to fostering critical thinking in Qur’an-Hadith learning. A qualitative descriptive approach with a textual-empirical orientation was employed. Textual analysis examined the concept of tafakkur in the Qur’an and its interpretations in exegetical sources, while empirical data were collected through observation, interviews, and documentation of Qur’an-Hadith learning at MA Darussalam Ngesong Jombang. The data were analyzed through data reduction, data display, and conclusion drawing, with credibility established through source and technique triangulation. The findings indicate that tafakkur can be conceptualized as Qur’anic reflective reasoning that progresses from observing Allah’s signs to constructing ethical meaning. This pedagogical concept was formulated into five interconnected learning stages: observing, questioning, reflecting, reasoning, and ethical meaning-making. Its application facilitates students’ more reflective, analytical, and meaningful engagement with Qur’an-Hadith texts. The study concludes that tafakkur provides a Qur’an-based pedagogical framework capable of integrating reflective reasoning, critical inquiry, and ethical formation. These findings contribute to the development of Qur’anic pedagogy and offer practical implications for designing Qur’an-Hadith instruction that moves beyond information transmission toward reflective-critical and ethically oriented learning.